World Dance Day: A Cultural Conservation in Maintaining Local Wisdom of Traditional Arts - Ana Rosmiati; Supriyanto Supriyanto; Joko Budiwiyanto; Tubagus Mulyadi (Institut Seni Indonesia Surakarta, 2022)
The research entitled